The relationship between e-trust and e-loyalty: The mediating role of e-satisfaction - Margaretha, Yolla; Hadianto, Bram; Pandjaitan, Dorothy Rouly Haratua (International Journal of Management and Sustainability, 2024)
This investigation proposes to verify the effect of e-satisfaction and e-trust on e-loyalty and the impact of e-trust on e-satisfaction. Besides, it attempts to prove e-satisfaction as the mediating variable. Therefore, this investigation applies the quantitative design by formulating the hypotheses. Additionally, the users of Shopee, one of the e-commerce platforms in Indonesia, become the population in this investigation. Because its accurate number is unknown, this study uses snowball sampling. As a result, this technique can acquire 175 respondents from some cities and regencies in Indonesia. Because of hypothesis verification, this research applies the covariance-based structural equation model (CBSEM) to check the causal relationship based on the first, second, and third premises. Besides, this study employs the Sobel technique to prove the e-satisfaction mediating impact. After checking the hypotheses, this study effectively verifies three substances. Firstly, the more electronically satisfied and trusting the users are, the more electronically loyal they are. Secondly, the more virtually they believe, the more virtually they are gratified. Finally, e-satisfaction can partially mediate the association between e-trust and e-loyalty. Expressively, e-trust is the driver of e-satisfaction, causing e-loyalty; therefore, as an implication, this study suggests that this platform needs to keep e-trust by providing safe transactions and privacy data protection for the users.